Ethnicity and Political Violence in Nigeria: The Case Study of 2023 General Elections in Lagos State - Kadiri , John Aigboje; Jeremiah, Michael Esele (Kashere Journal of Politics and International Relations, 2023)
The study therefore bridged this gap by examining ethnicity and political violence in Lagos State during the 2023 general elections. The study set to achieve five objectives: to examine whether or not ethnic politics occurred during the 2023 General Elections in Lagos State; to examine the cause of ethnic politics during the 2023 General Elections in Lagos; to examine whether or not political violence occurred during the 2023 General Elections in Lagos State; to understand the effect of ethnicity on political violence during the 2023 General Elections in Lagos State; and to proffer solutions to ethnic politics in Nigeria. The study sampled 195 respondents and utilized both open and close-ended questionnaire to elicit responses from the respondents who were adult residents in Lagos State. The study found that ethnic politics and political violence did occur during the 2023 General Elections in Lagos State. It also found that there is a significant relationship between ethnicity and political violence during the 2023 General Elections in Lagos State. It was also found that the major cause of the ethnic politics was a quest for political power by candidates. The study therefore recommended that the law, judiciary and law enforcement agencies should take appropriate actions against political elites who utilize the instrument of ethnicity to influence electoral outcomes. Furthermore, the study recommended that an alternative compensatory position for any candidate that loses an election. By this, the zero-sum nature of Nigeria’s electoral process would have been reduced.